Effect of foliar and soil application of nitrogen on the growth and yield of wheat - Islam, MS; Akter, H; Aktar, S; Miah, MJ; Farazi, M (Progressive Agriculture, 2018)
A pot experiment was conducted at the Bangladesh Institute of Nuclear Agriculture, Mymensingh during the period from November 2013 to March 2014 to examine the effect of nitrogen application methods on the growth and yield of wheat. Two application methods (Foliar spray and soil application) and three varieties viz. Sotabdi, Kanchan and BAW56 were included and experimental test crop. From the study it was found that plant height. Total tillers plant-1,effect tillers plant-1,root dry weight plant-1,grains panicle-1, 100 grain weight, grain weight plant-1, straw weight plant-1, biological yield plant-1, and harvest indexwere significantly higher by foliar spray method than the soil application of nitrogen, Higher grain yield (9.01 g plant-1) was observed by the foliar spray application and lower grain yield was 6.07 g plant-1 obtained from the soil application. Among 3 varieties Sotabdi was found to be better yielding ability and produced comparatively higher plant height, total tillers plant-1, effective tillers plant-1,root dry weight plant-1, grains panicle-1, 100 grains weight, grains weight plan-1, straw weight plant-1, biological yield plant-1, in respect of harvest index values. BAW56 was observed as medium performed variety and Kanchan was the least. Regarding interaction effect of the variety Sotabdi also showed the highest plant-1, total tillers plant-1, effective tillers plant-1, root dry weight plant-1, grains panicle-1,100 grains weight, grains weight plant-1, straw weight plant-1, biological yield plant-1 and harvest index by foliar spray. The results indicated that all the varieties gave higher grain yields under foliar spray application method. Progressive Agriculture 28 (4): 287-294, 2017